Diskriminasi Perempuan dalam Pupulan Cerpen Tatu Anak Luh Pendekatan Feminisme - Widiantara, I Wayan; Suteja, I Wayan; Puspawati, Luh Putu (Humanis; Vol 25 No 1 (2021), 2021)
This study is entitled "Discrimination of Women in Pupulan Tatu Anak Luh Short Stories Feminsime Approach" by discussing three short stories namely Tatu Anak Luh short stories, Mejalan Tanpa Batis and Mepasung Ulian Warisan with the feminsime approach. Research on Pupil Tatu Anak Luh Short Story discusses the analysis of the structure and discrimination of women in the form of violence. This analysis aims to reveal the structure and violence contained in the short story of Tatu Anak Luh. This research uses structural theory and feminism theory. The methods and techniques used in this study were divided into three stages, namely: (1) methods and data collection techniques using the listening method assisted with translation and note-taking techniques. (2) data analysis methods and techniques using qualitative methods and analytic descriptive techniques. (3) methods and techniques for presenting the results of data analysis using informal methods assisted with deductive-inductive techniques. The results obtained from this study, namely the narrative structure consisting of incidents, plot, character and characterization, setting, theme, and mandate. In addition, this study also revealed female discrimination, in the form of verbal violence, physical violence and mental or psychological violence.